Absolute configuration reassignment of two chromanes from Peperomia obtusifolia (Piperaceae) using VCD and DFT calculations - Batista, Joao Marcos [UNESP]; Batista, Andrea N. L. [UNESP]; Rinaldo, Daniel [UNESP]; Vilegas, Wagner [UNESP]; Cass, Quezia B.; Bolzani, Vanderlan da Silva [UNESP]; Kato, Massuo J.; Lopez, Silvia N. [UNESP]; Furlan, Maysa [UNESP]; Nafie, Laurence A. (Pergamon-Elsevier B.V. Ltd, 2010)
Previous analysis of the ECD spectra of two prenylated benzopyrans isolated from Peperomia obtusifolia, by means of the helicity rule for the chromane chromophore, resulted in the incorrect assignment of their absolute configuration, (5) instead of (R) for a deduced P-helicity of the chromane ring for the (+)-enantiomers. This was discovered by the application of DFT calculations and VCD spectroscopy. Experimental and calculated (B3LYP/6-31G(d)) VCD and IR spectra were compared, and a definitive absolute configuration of (+)-1 and (+)-2 is reassigned directly in solution as (R). The assumption of equatorial positioning of bulky groups, shown here to be invalid for the title molecules, is the underlying cause of the previous incorrect assignment of absolute configuration. Moreover, TDDFT (B3LYP/6-311++G(2d,2p)//B3LYP/6-31G(d)) calculations of ECD spectra have shown that both P- and M-helicity of the heterocyclic ring, for a given absolute configuration, lead to the same sign for the (1)L(b) ECD band, thus bringing into question the validity of the empirical ECD helicity rule for chromane molecules. (C) 2010 Elsevier Ltd. All rights reserved.